2021
DOI: 10.3390/jcm10061163
|View full text |Cite
|
Sign up to set email alerts
|

A Diagnostic Algorithm Based on a Simple Clinical Prediction Rule for the Diagnosis of Cranial Giant Cell Arteritis

Abstract: Background: Risk stratification based on pre-test probability may improve the diagnostic accuracy of temporal artery high-resolution compression sonography (hrTCS) in the diagnostic workup of cranial giant cell arteritis (cGCA). Methods: A logistic regression model with candidate items was derived from a cohort of patients with suspected cGCA (n = 87). The diagnostic accuracy of the model was tested in the derivation cohort and in an independent validation cohort (n = 114) by receiver operator characteristics … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…It should be noted that imaging test results should always be interpreted in the context of the level of suspicion of GCA, which is generally based on the clinical judgment and experience of the physician treating patients with GCA. Efforts have been made by different expert groups to develop pre-test clinical probability scores for GCA to help clinicians estimate the likelihood of GCA [65,66]. These scores can be potentially useful in ensuring a more homogeneous management of patients with GCA and in optimizing the performance of imaging techniques.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that imaging test results should always be interpreted in the context of the level of suspicion of GCA, which is generally based on the clinical judgment and experience of the physician treating patients with GCA. Efforts have been made by different expert groups to develop pre-test clinical probability scores for GCA to help clinicians estimate the likelihood of GCA [65,66]. These scores can be potentially useful in ensuring a more homogeneous management of patients with GCA and in optimizing the performance of imaging techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple authors have suggested employing clinical algorithms to improve diagnostic protocol ( 19 – 21 ). Some preliminary algorithm models suggest that GCA diagnosis can be achieved through a combination of demographic information, a detailed history, physical exam, and fundoscopic findings ( 20 ). We highly recommend developing such an algorithm with stronger consideration for age and clinical manifestations before the performance of a TA biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…If available, histological results of temporal artery biopsy (TAB) were collected. Based on clinical symptoms, the presence of anterior ischaemic optic neuropathy and the Creactive protein (CRP)-values, a previously published clinical prediction score for cranial GCA was calculated (15,16). As the 1990 American College of Rheumatology are not useful for diagnosis of extracranial GCA (11) and related to advances in non-invasive imaging temporal artery biopsy nowadays is dispensable in many patients (8), we applied modified disease classification criteria (16,17).…”
Section: Patient Characteristicsmentioning
confidence: 99%